Beethoven Cycle of Radio-Paris May-June 1943 - Radio Paris::::::::::::::: (Curiel-Archereau; Paris; France, 2020)
Programs of Beethoven performances by the orchestra of Radio-Paris under the direction of Willem Mengelberg in May-June, 1943. Includes photographs of the performers.